La Lisozima Como Conservante Natural En La Elaboración De Quesos Semi-Maduros - Villa, Diana; Osorio, Miguel; Mejía, Teresita; Toledo, Norma; Haro, Juan; Quevedo, Luis (European Scientific Journal, ESJ, 2017)
In the IASA II Molestina Dairy Plant, different levels of lysozyme were evaluated as a natural preservative (5, 10 and 15%). This replaces the chemical preservative (sorbic acid E300) in the production of Andean cheese (“semimaduro”). By using 256 liters of milk divided into 32 experimental units of 4 liters each, the experimental results were subjected to analysis of variance and separation of means by the Waller-Duncan test. It also went through the Test of Rating Test for organoleptic characteristics. Determining the levels of lysozyme did not affect the physico- chemical properties of cheese. It presents an average content of 37.46% moisture, 26.53% protein, 25.53% fat, 5.65% ash, and a slightly acidic pH (6.04). The preference of consumers according to the organoleptic characteristics shows that there were no differences between cheeses, receiving a score of Very Good. The initial microbiological tests identified the absence of total coliforms, molds and yeasts, which is in contrast to the 21 days of storage (shelf life). Lower amounts of microorganisms increases the levels of lysozyme, and provides better Employment answers level of 15%. The highest yield (10.25%), as well as lower production costs (4.89 USD per kg), were obtained when we prepared the semi-mature cheese with 15% of lysozyme in place of chemical preservatives. So this level is recommended in the development of Andean type cheeses.